Poly-L-arginine grafted silica mesoporous nanoparticles for enhanced cellular uptake and their application in DNA delivery and controlled drug release - Kar, Mrityunjoy; Tiwari, Neha; Tiwari, Mitali; Lahiri, Mayurika; Sen Gupta, Sayam (Particle & Particle Systems Characterization, 2013)
Mesoporous silica nanoparticles (MSNs), that are capable of delivering gene and drugs to organisms in an effective and selective way have attracted much attention lately for its potential in the treatment of cancer. However, the successful application of MSNs for delivery of plasmid DNA or drugs requires surface modification of the silica with positively charged functional groups so that it binds to the negatively charged nucleic acids and also helps it penetrate through the cell membrane. We report for the first time the synthesis of a hybrid MSN where the cell penetrating cationic polypeptide poly-L-arginine synthesized by NCA polymerization is grafted onto the external surface of MSN using click chemistry. These poly-L-arginine grafted MSNs show low cytotoxity (85% cell viability at 100 g/mL MSN concentration) and high cellular uptake by both HeLa and A549 (>90%). The poly-L-arginine grafted MSNs were used effectively to deliver mCherry DNA plasmid into cells leading to expression of the protein mCherry inside the cells (transfection efficiency 60%). In contrast, poly-L-arginine grafted non-porous silica nanoparticles were unable to express the protein mCherry inside the cells although their uptake into the cells was as efficient as with poly-L-arginine grafted MSNs. We also show preliminary results to demonstrate that these hybrid MSNs can be used as a delivery vehicle for the anticancer drug Doxorubicin towards cancerous cells HeLa and A549. The biocompatibility of poly-L-arginine and its cell penetrating ability are expected to make these MSN conjugates very useful carriers for the delivery of genes and drugs into cancer cells.

Drug-triggered self-assembly of linear polymer into nanoparticles for simultaneous delivery of hydrophobic and hydrophilic drugs in breast cancer cells - Palvai, Sandeep; Anandi, Libi; Sarkar, Sujit; Augustus, Meera; Roy, Sudip; Lahiri, Mayurika; Basu, Sudipta (ACS Omega, 2017)
Breast cancer is the most devastating disease among females globally. Conventional chemotherapeutic regimen relies on the use of highly cytotoxic drugs as monotherapy and combination therapy leading to severe side effects to the patients as collateral damage. Moreover, combining hydrophobic and hydrophilic drugs create erratic biodistribution and suboptimal medicinal outcome. Hence, packaging multiple drugs of diverse mechanisms of action and biodistribution for safe delivery into tumor tissues with optimal dosages is indispensable for next-generation breast cancer therapy. To address these, in this report, we describe a unique cisplatin-triggered self-assembly of linear polymer into 3D-spherical sub 200 nm particles. These nano-particles comprise a hydrophobic (paclitaxel) and hydrophilic drug (cisplatin) simultaneously in a single particle. Molecular dynamics simulation revealed hydrophilic-hydrophilic interaction and interchain H-bonding as underlying mechanisms of self-assembly. Confocal microscopy studies evidently demonstrated that these novel nanoparticles can home into lysosomes in breast cancer cells, fragment subcellular nuclei, and prevent cell division, leading to improved breast cancer cell death compared to free drug combination. Moreover, 3D-breast tumor spheroids were reduced remarkably by the treatment of these nanoparticles within 24 h. These dual-drug-loaded self-assembled polymeric nanoparticles have prospective to be translated into a clinical strategy for breast cancer patients.

Multifunctional luminogens with synergy of aggregation-induced delayed fluorescence, two-photon absorption and photocurrent generation - Chatterjee, Abhijit; Narayanan, Sundaravalli; Thorat, Sachin; Malik, Ajay J.; Ambhore, Madan D.; Narayanan, Aswini; Sihag, Anil Kumar; Babu, Sukumaran Santhosh; Lahiri, Mayurika; Hazra, Partha (Chemical Communications, 2025)
In this study, we investigated the aggregation-induced delayed fluorescence (AIDF) properties of three luminogens - TN, TA, and TP. Our comprehensive theoretical analysis reveals a significant reduction in the Delta EST in their aggregated or solid-state, activating TADF, on a similar to mu s time-scale. Additionally, these luminogens demonstrate two-photon excited anti-Stokes photoluminescence emission and improved photocurrent generation, attributed to their strong charge transfer characteristics and longer singlet exciton lifetimes.